THE EFFECT OF PRICE AND PRODUCT QUALITY TOWARDS CUSTOMER LOYALTY OF TELKOMSEL INTERNET PACKAGE USERS (CASE STUDY: INTERNATIONAL BUSINESS ADMINISTRATION STUDENTS AT SAM RATULANGI UNIVERSITY) - Aneilla Tessalonika Gleny Ruth Laserto; Shinta J. C. Wangke (Universitas Sam Ratulangi, 2023)
The purpose of this study is to ascertain whether Telkomsel customers remain devoted to current promotions. This study uses quatitative methods and uses multiple linear regression tests to determine the effect of Price and Product Quality towards Customer Loyalty. The sample for this study was 100 respondents. The sampling technique used is the purposive sampling method and data collection method in the form of a questionnaire run through Google Form. Testing and analysis of data in this study using SPSS 22 software. The results showed that Price (X1) partially had a positive and significant effect on Customer Loyalty (Y). Product Quality (X2) has a partial positive and significant effect on Customer Loyalty (Y). Perceived Value (X1) and Brand Experience (X2) simultaneously have a positive and significant effect on Customer Loyalty (Y). The value of the coefficient of determination (R2) is 0.633 or 63.3% meaning that the independent variables in this study have an effect of 63.3% on customer loyalty and the remaining 36.7% comes from external factors or variables that are not discussed or explained in this study. Keyword: price, product quality, customer loyalty